(untitled) (The Review of Diabetic Studies, 2022)
OBJECTIVE: To assess the prevalence of patients at risk of developing diabetic foot complications(i.e. foot at-risk) and its clinical components according to the updated International Working Group on Diabetic Foot (IWGDF) criteria and to describe demographic and diabetes-related characteristics. METHODS: We conducted a cross-sectional study at María Auxiliadora Hospital between 2017 and 2018. The criteria for foot at-risk in the IWGDF 2019 risk stratification system are classified into four risk categories, R0-R3, ranging from no peripheral arterial disease (PAD) and no peripheral neuropathy (PN) to the presence of PAD or PN in combination with previous foot ulcer, amputation, or endstage renal disease (R3). According to this system, we obtained prevalence ratios (PR) of foot at-risk categories dependent on sex, age, diabetes duration, and Total Symptom Score. A sample size of 402 subjects was included in the study. RESULTS: Subjects included had a mean age of 61 years, and 66% were female. There were no patients with type 1 diabetes, and 59% percent had a diabetes duration of less than ten years. The prevalence of foot at-risk was 54.3% defined by the IWGDF 2019 criteria, which gave prevalence17% higher than that defined with the previous 1999 criteria. PN and PAD frequency was 37.3% and 30.1%, respectively. Foot at-risk prevalence was 40% higher in those with severe Total Symptom Score (PR 1.40, 95% CI 1.09-1.80) and also 39% higher in men than in women (PR 1.39, 95% CI 1.17-1.64). Likewise, diabetes duration of more than ten years had a 25% higher prevalence of foot at-risk (PR 1.25, 95% CI 1.05-1.49), and those older than 60 years had a 20% higher presence of this condition (PR 1.20, 95% CI 1.001- 1.43). CONCLUSIONS: Our hospital faces a substantial burden of diabetic foot risk in men, patients with long diabetes duration, and those with painful neuropathy. More initiatives are required at primary or hospital level to detect this critical condition. Likewise, reference centers with multidisciplinary teams to apply prevention and therapeutic interventions are urgently needed.